2014
DOI: 10.1111/jam.12495
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods for the control of postharvest citrus diseases

Abstract: Summary The postharvest diseases of citrus fruit cause considerable losses during storage and transportation. These diseases are managed principally by the application of synthetic fungicides. However, the increasing concern for health hazards and environmental pollution due to chemical use has required the development of alternative strategies for the control of postharvest citrus diseases. Management of postharvest diseases using microbial antagonists, natural plant‐derived products and Generally Recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
135
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 125 publications
(169 reference statements)
2
135
0
10
Order By: Relevance
“…The present study utilized a similar approach by obtaining yeast isolates collected from cold soils in the region of Tibet, and demonstrated that this approach could be used to identify effective, potential biocontrol agents. The use of wounded/inoculated pear fruit is an efficient method for identifying yeasts that could be potentially used to manage postharvest rots (Kaoud 2014). After a preliminary screening test, four yeast isolates with biocontrol activity were selected for further study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study utilized a similar approach by obtaining yeast isolates collected from cold soils in the region of Tibet, and demonstrated that this approach could be used to identify effective, potential biocontrol agents. The use of wounded/inoculated pear fruit is an efficient method for identifying yeasts that could be potentially used to manage postharvest rots (Kaoud 2014). After a preliminary screening test, four yeast isolates with biocontrol activity were selected for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Apple cultivars are susceptible to various pathogens including Penicillium expansum or Botrytis cinerea that can cause losses during the postharvest period. Biocontrol of postharvest diseases depends on the specific pathogen and biocontrol agent (Teixidó et al, 2011;Talibi et al, 2014). Typically, chemical treatments, including methyl bromide, are used to control postharvest diseases of apples.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing concern for health hazards and environmental pollution due to the use of chemicals has required the development of alternative strategies for the control of postharvest citrus diseases. Management of postharvest diseases using microbial antagonists, natural plant-derived products and compounds that are generally recognised as safe has been demonstrated to be most suitable to replace the synthetic fungicides, which are either being banned or recommended for limited use (Smilanick et al 2005;Sharma et al 2009;Talibi et al 2014).…”
mentioning
confidence: 99%